Effect of Some Plants Extracts on the Mortality of the 4th Larval Instar Mosquitoes Culex quinquefasciatus - Hasan S. AL-Dhaher, Areej (Al-Qadisiyah Journal of Pure Science, 2021)
In this study, the effect of water and alcoholic (ethanol) extracts of Caper Bush Capparis spinosa L., Cumine Cuminum cyminum L. , Black pepper Piper nigrum L., Sage Salvia sp. and Cat thyme Teucrium polium L. plants on the 4th instar larvae of Culex quinquefasciatus have been evaluated .The results showed that the water extract of P. nigrum had the highest effect on the larvae, with 48h LC50 155. 9 ppm followed by ethanol extracts of C. cyminum , C. spinosa and P. nigrum with 48h LC50 308.2 ,315.1and 791.4 ppm respectively. For all studied plants, the secondary compounds were identified. Alkaloids and phenol extracts from Capparis spinosa, Alkaloids, flavonoids and volatile oils from Cuminum cyminum and Alkaloids and volatile oils from Piper nigrum had been isolated. The volatile oils and alkaloids extracts of P. nigrum showed the highest effect with 48h LC50 values 6.3 and 10.2 ppm, respectively then the volatile oil extract and alkaloids extract of C. cyminum with 48h LC50 were 21.1 and 429.4 ppm respectively